The Psychometric Properties of the Norwegian version of Adult ADHD Self Report Scale, 1.1 (ASRS) - Kornør, Hege; Hysing, Mari (PsykTestBarn, 2011)
Description: The ASRS is a self-rating questionnaire for mapping ADHD symptoms in adolescents and adults. It takes approximately five minutes to complete. The WHO Workgroup on Adult ADHD published the original version in 2005, and the Norwegian translation in 2008. The World Health Organization does not specify any test-related or professional requirements for use of the ASRS, but interpretation of the ASRS as part of a supplement in a diagnostic process should be done by qualified health professionals. Literature search: Our systematic literature search identified three publications from one Norwegian study that used an ASRS version other than the official translation. As the wording of this version was sufficiently similar to the official translation, and the translation process was correct, we decided to include the three publications. Psychometrics: None of the three included publications contained psychometric data. Users of the ASRS in clinical practice should apply caution. Konklusjon: There is a need for research on the psychometric properties of this instrument.